Self-Care Practice in Social Work Education: A Systematic Review of Interventions. (2nd January 2019) - Griffiths, Austin; Royse, David; Murphy, April; Starks, Saundra
ABSTRACT: Social work is a demanding profession as practitioners routinely face difficult situations that affect their well-being. The National Association of Social Workers strongly supports self-care practice as an approved mechanism to offset these challenges, yet practitioners report not learning techniques necessary to perform self-care. In this study, a systematic review compliant with Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards was conducted to identify evidence-based interventions used to improve student self-care practice in social work education. In the four studies meeting inclusion criteria, mindfulness practice was the only empirically evaluated self-care strategy reported—and with mixed results. Mindfulness activities enable social workers to sustain their well-being and is critical to modeling and providing effective service delivery to clients. Areas for further research are indicated.